2014
DOI: 10.19030/jier.v10i2.8515
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Service Quality In Higher Education: A South African Case Study

Abstract: The goal of this paper is to report on the SERVQUAL gap which causes unsuccessful service delivery at a University of Technology in South Africa. Using a quantitative research design, the study adopts a SERVQUAL model adapted to a tertiary environment containing five dimensions of service quality (tangibles, responsiveness, empathy, assurance, and reliability). A convenience sampling technique was applied, the data were collected from 280 respondents at the Durban University of Technology (DUT), and the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 18 publications
2
34
0
9
Order By: Relevance
“…To provide excellent cus-tomer service is a necessity in the organizational manager's ability to maintain customer satisfaction and loyalty, meet profitability goals, and obtain a competitive advantage [32] [33]. Green (2014) [34] stated that customer service is difficult to measure because customer service includes customer expectations, and every customer has different expectations. A customer will rate the customer service experience on expectations of the service provider's ability to meet the expectations [2].…”
Section: Customer Service Philosophymentioning
confidence: 99%
“…To provide excellent cus-tomer service is a necessity in the organizational manager's ability to maintain customer satisfaction and loyalty, meet profitability goals, and obtain a competitive advantage [32] [33]. Green (2014) [34] stated that customer service is difficult to measure because customer service includes customer expectations, and every customer has different expectations. A customer will rate the customer service experience on expectations of the service provider's ability to meet the expectations [2].…”
Section: Customer Service Philosophymentioning
confidence: 99%
“…The study showed significant variables in explaining student satisfaction as follows: trust developed toward the university and the academic program, and the perception they have of assessment techniques as a challenge to improve intellectual growth. Finally, Green (2014) has elaborated the service quality in higher education. The study revealed that, on average, customers have higher expectation in tangibles, reliability, and assurance.…”
Section: Service Quality In Higher Education Institutionmentioning
confidence: 99%
“…Διάφορα ερωτηματολόγια, όπως το Servqual, ή αλλιώς κλίμακες όπως είναι το HedPERF, το SerVPERF, με το HedPERF να έχει μια υπεροχή (Abdullah, 2006) και γενικά ερωτηματολόγια ή μοντέλα ποιότητας έχουν χρησιμοποιηθεί με στόχο την αξιολόγηση των υπηρεσιών και που προσαρμόζονται στις ανάγκες αξιολόγησης του κάθε ιδρύματος όπως είναι το μοντέλο αξιολόγησης HEGAM το οποίο περιλαμβάνει και κριτήρια για τις ηλεκτρονικές υπηρεσίες (Noaman και συν., 2013) και το οποίο έδωσε σημαντικές κατευθυντήριες στην ηγεσία του Πανεπιστημίου για να πετύχει την απαιτούμενη ποιότητα των υπηρεσιών αλλά και έναν από τους στρατηγικούς στόχους του που ήταν να γίνει ένα ηλεκτρονικό πανεπιστήμιο με λιγότερη γραφειοκρατία. Άλλες σχετικές έρευνες χρησιμοποίησαν τα προαναφερθέντα εργαλεία για να αξιολογήσουν την ποιότητα των παρεχόμενων προς τους φοιτητές υπηρεσιών στην τριτοβάθμια εκπαίδευση και διαπίστωσαν ότι υπάρχει ανάγκη να δοθούν κίνητρα στους φοιτητές/χρήστες για να εκφράσουν τις απαιτήσεις και τις γενικές τους ανησυχίες προκειμένου να συμβάλουν στη βελτίωσή τους (Gemmel & Pagano, 2003), η βελτίωση της ποιότητας προϋποθέτει τη μέτρησή της και βοηθάει στο να δημιουργηθεί μια αγορά για τα δημόσια πανεπιστήμια η οποία να είναι προσανατολισμένη περισσότερο στο φοιτητή (Cerri, 2012) και επίσης, ότι το Servqual μπορεί να αναδείξει σημαντικούς παράγοντες ποιότητας όπως είναι τα εμπράγματα στοιχεία, η αξιοπιστία και η ασφάλεια που σχετίζονται με την ικανοποίηση των φοιτητών (Khodayari F. & Khodayari, B., 2011, Govender και συν., 2014 αλλά και την ικανοποίηση του προσωπικού (Green, 2014). Στον ελληνικό χώρο, σε έρευνα για την αξιολόγηση των παρεχόμενων προς τους φοιτητές ηλεκτρονικών υπηρεσιών τριτοβάθμιου εκπαιδευτικού ιδρύματος οι φοιτητές δήλωσαν ότι χρησιμοποιούν πολύ τις διαδικτυακές εφαρμογές, ενώ όλοι συμφωνούσαν στην ανάγκη ύπαρξης wi-fi δικτύου σε όλους τους χώρους του Πανεπιστημίου (Μπάκος, 2013).…”
Section: ανασκόπηση συναφών ερευνώνunclassified